MORTALITY IN ANESTHESIA: A SYSTEMATIC REVIEW - Braz, Leandro Gobbo [UNESP]; Braz, Danilo Gobbo; da Cruz, Deyvid Santos [UNESP]; Fernandes, Luciano Augusto [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Cerqueira Brazi, Jose Reinaldo [UNESP] (Universidade de São Paulo (USP), Hospital das Clínicas, 2009)
This systematic review of the Brazilian and worldwide literature aims to evaluate the incidence and causes of perioperative and anesthesia-related mortality. Studies were identified by searching the Medline and Scielo databases, followed by a manual search for relevant articles. Our review includes studies published between 1954 and 2007. Each publication was reviewed to identify author(s), study period, data source, perioperative mortality rates, and anesthesia-related mortality rates. Thirty-three trials were assessed. Brazilian and worldwide studies demonstrated a similar decline in anesthesia-related mortality rates, which amounted to fewer than 1 death per 10,000 anesthetics in the past two decades. Perioperative mortality rates also decreased during this period, with fewer than 20 deaths per 10,000 anesthetics in developed countries. Brazilian studies showed higher perioperative mortality rates, from 19 to 51 deaths per 10,000 anesthetics. The majority of perioperative deaths occurred in neonates, children under one year, elderly patients, males, patients of ASA III physical status or poorer, emergency surgeries, during general anesthesia, and cardiac surgery followed by thoracic, vascular, gastroenterologic, pediatric and orthopedic surgeries. The main causes of anesthesia-related mortality were problems with airway management and cardiocirculatory events related to anesthesia and drug administration. Our systematic review of the literature shows that perioperative mortality rates are higher in Brazil than in developed countries, while anesthesia-related mortality rates are similar in Brazil and in developed countries. Most cases of anesthesia-related mortality are associated with cardiocirculatory and airway events. These data may be useful in developing strategies to prevent anesthesia-related deaths.
Keywords: Anesthesia; Cardiac Arrest; Mortality; Perioperative; Review